Gas‐phase Acidities of 2‐Aryl‐2‐chloro‐1, 1, 1‐trifluoroethanes and Related Compounds. Experimental and Computational Studies. (25th May 2016) - Mishima, Masaaki; Abboud, José‐Luis M.; Fujio, Mizue; Suenaga, Masahiko; Koch, Heinz F.; Koch, Judith G.
Abstract: The gas‐phase acidities (GA) of 2‐aryl‐2‐chloro‐1, 1, 1‐trifluoroethanes (1a ), 2‐aryl‐2‐fluoro‐1, 1, 1‐trifluoroethanes (2a ), and related compounds, XC6 H4 CH(Z)R where Z = Cl (1 ) or F (2 ) and R = C2 F5 (b ), t ‐C4 F9 (c ), C(CF3 )2 C2 F5 (d ), C(CF3 )2 Me (e ), Me (f ), H (g ), were investigated experimentally and computationally. On the basis of an excellent linear correlation ( R 2 > 0.99) of acidities of1c, 1d, 1e, 1f and2c, 2d, 2e, 2f where there is no fluorine atom at β‐position to thedeprotonation site with the corrected number of fluorine atoms contained in the fluorinated alkyl group, the extent of β‐fluorine negative hyperconjugation of the CF3 and C2 F5 groups ( ΔG o β‐F ) was evaluated. The GA el values given by subtraction ΔG o β‐F from the apparent GA value were considered to represent the electronic effect of the substituent X. The substituent effects on the GA el values and GA values for1c, 1d, 1e, 1f and2c, 2d, 2e, 2f were successfully analyzed in terms of the Yukawa–Tsuno equation. The variation of resonance demand parameter r − with the R group observed for various XC6 H4 CH(Z)R was linearly related to the GA ( GA el ) value of the respective phenyl‐substituted fluorinated alkanes. On the other hand, the corresponding correlation for the ρ values provided three lines for ArCH(Cl)R, ArCH(F)R and ArCH2 R, respectively. These results supported our previous conclusion that the r − and ρ values are governed by the thermodynamic stability of the parent ion (ring substituent = H). Other factors arising from an atom bonded to the acidic center also influence the ρ value. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The β‐fluorine negative hyperconjugation of the CF3 and C2 F5 groups ( ΔG 0 β‐F ) and electronic effect of the aryl group ( GA el ) involved in the gas‐phase acidities of1a, b and2a, b were evaluated. The substituent effects on the GA el and GA values of various aryl‐substituted fluoroalkanes were analyzed.